Development and validation of a survey for well-being and interaction assessment by occupants in office buildings with adaptive facades. (15th June 2019) - Attia, S.; Garat, S.; Cools, M.
Abstract: Assessing well-being and occupants satisfaction is a growing concern in façade design practice, as increasing recognition of the value of well-being of occupants in office buildings. The objective of this study was to develop a validated survey for evaluating the indoor environmental quality in office buildings with adaptive facades to provide feedback to designers and operators and inform the building community at alarge. A total of 70 employees completed an initial survey containing 14 questions grouped into six domains (OCAFAS-14). Factor analysis of the responses was performed resulting into a final survey grouped into three domains and containing 15 questions (general feeling, thermal comfort and acoustic comfort) (OCAFAS-15). Statistical analysis indicated that the OCAFAS-15 had good validity, reliability, and internal consistency. The survey succeeded to benchmark well-being, satisfaction and interaction changes of employees in an open-space office with dynamic louvers. The results indicates that the OCAFAS-15 provides a basis for dialogue between occupants and façade engineers regarding the user interaction, façade control adaptation and in particular in tracking of changes of indoor environmental quality, evaluating response of facades to occupants' requirements, and guiding the operation of adaptive facades. A validated well-being and occupant interaction survey could be particularly useful in benchmarking building with adaptive facades and recognizing and managing occupants' dissatisfaction in buildings with dynamic facades. Highlights: A survey for evaluating well-being and occupants interaction was developed. A total of 70 employees completed an initial survey containing 14 items. Based on factor analysis of responses a final survey with 15 items was validated. The survey is useful in benchmarking buildings with adaptive facades. The survey is useful in managing occupants' needs in buildings with movable shading.